Determination of growth hormone releasing peptides metabolites in human urine after nasal administration of GHRP‐1, GHRP‐2, GHRP‐6, Hexarelin, and Ipamorelin. Issue 10 (13th April 2015) - Semenistaya, Ekaterina; Zvereva, Irina; Thomas, Andreas; Thevis, Mario; Krotov, Grigory; Rodchenkov, Grigory
<x xml:space="preserve">Abstract</x> Growth hormone releasing peptides (GHRPs) stimulate secretion of endogenous growth hormone and are listed on the World Anti‐Doping Agency (WADA) Prohibited List. To develop an effective method for GHRPs anti‐doping control we have investigated metabolites of GHRP‐1, GHRP‐2, GHRP‐6, Hexarelin, and Ipamorelin in urine after nasal administration. Each compound was administrated to one volunteer. Samples were collected for 2 days after administration, processed by solid‐phase extraction on weak cation exchange cartridges and analyzed by means of nano‐liquid chromatography ‐ high resolution mass spectrometry. Six metabolites of GHRP‐1 were identified. GHRP‐1 in the parent form was not detected. GHRP‐1 (2‐4) free acid was detected in urine up to 27 h. GHRP‐2, GHRP‐2 free acid and GHRP‐2 (1‐3) free acid were detected in urine up to 47 h after administration. GHRP‐6 was mostly excreted unchanged and detected in urine 23 h after administration, its metabolites were detectable for 12 h only. Hexarelin and Ipamorelin metabolized intensively and were excreted as a set of parent compounds with metabolites. Hexarelin (1‐3) free acid and Ipamorelin (1‐4) free acid were detected in urine samples after complete withdrawal of parent substances. GHRPs and their most prominent metabolites were included into routine ultra‐pressure liquid chromatography‐tandem mass spectrometry procedure. The method was fully validated, calibration curves of targeted analytes were obtained and excretion curves of GHRPs and their metabolites were plotted. Our results confirm that the detection window after GHRPs administration depends on individual metabolism, drug preparation form and the way of administration. Copyright © 2015 John Wiley & Sons, Ltd.